Slavery in the late antique world, 150-700 CE - De Wet, Chris L., 1982-; Kahlos, Maijastina, 1967-; Vuolanto, Ville, 1971- (Cambridge University Press, 2022)
Slavery in the Late Antique World, 150-700 CE investigates the ideological, moral, cultural, and symbolic aspects of slavery, as well the living conditions of slaves in the Mediterranean basin and Europe during a period of profound transformation. It focuses on socially marginal areas and individuals on an unprecedented scale. Written by an international team of scholars, the volume establishes that late ancient slavery is a complex and polymorphous phenomenon, one that was conditioned by culture and geography. Rejecting preconceived ideas about slavery as static and without regional variation, it offers focused case studies spanning the late ancient period. They provide in-depth analyses of authors and works, and consider a range of factors relevant to the practice of slavery in specific geographical locations. Using comparative and methodologically innovative approaches, this book revisits and questions established assumptions about late ancient slavery. It also enables fresh insights into one of humanity's most tragic institutions.